2016
DOI: 10.4317/jced.53049
|View full text |Cite
|
Sign up to set email alerts
|

Report of a case of acinic cell carcinoma of the upper lip and review of Japanese cases of acinic cell carcinoma of the minor salivary glands

Abstract: Acinic cell carcinoma (ACC) is a malignant tumor of the salivary glands. The majority of ACCs occur in the parotid gland, and ACCs of the minor salivary glands (MSGs) are relatively infrequent. We describe here a patient with ACC of the upper lip. The patient was a 31-year-old male who presented with a nodular mass on the left upper lip. The preoperative diagnosis was benign tumor or cyst, and the lesion was surgically excised. The histological diagnosis was ACC. The postoperative course was uneventful. No rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In contrast, smaller OC lesions may be difficult to recognize for family dentists with no specialization in oral surgery, as these smaller lesions generally mimic the characteristics of benign lesions. 17 , 18 , 25 , 26 Moreover, patients with smaller OC lesions generally do not experience any symptoms, 16 and patients with OC may have little knowledge of the disease. 27 , 28 Thus, patients with smaller OC lesions may not present with any complaints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, smaller OC lesions may be difficult to recognize for family dentists with no specialization in oral surgery, as these smaller lesions generally mimic the characteristics of benign lesions. 17 , 18 , 25 , 26 Moreover, patients with smaller OC lesions generally do not experience any symptoms, 16 and patients with OC may have little knowledge of the disease. 27 , 28 Thus, patients with smaller OC lesions may not present with any complaints.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the dentists' familiarity with gingival examinations also makes them accustomed to seeing severe gingival inflammation. Since gingival inflammation and malignancy are often similar in appearance, 17 , 18 , 25 family dentists may have a high threshold for the diagnosis of gingival malignancy, and they may diagnose a malignant gingival lesion as gingival inflammation, leading to prolonged referral delays. However, in the present study, the gingival site of OC was not a significant risk factor for referral delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al reported a case of acinic cell carcinoma that presented as an asymptomatic mucocele-like mass on an unusual site, the lower lip; after a clinical and histopathological diagnosis of acinic cell carcinoma, they performed surgical excision with a safety margin [ 6 ]. Ishikawa et al also reported a case of acinic cell carcinoma of the upper lip: the preoperative diagnosis was benign tumor or cyst, and the mass was thus surgically excised along the border with the normal tissues [ 7 ]. A case of mucoepidermoid carcinoma in which the clinical and radiographic investigations were suggestive of a mucocele (ranula) was described by Melo et al [ 8 ] The treatment of choice was the complete excision of the mucocele and left submandibular salivary gland.…”
Section: Discussionmentioning
confidence: 99%